Pengaruh Work Environment, Job Involvement, dan Job Satisfaction terhadap Turnover Intention pada PT. XYZ - Margareta Margareta; Christy Ayu Sarah Panjaitan; Erwin Winata (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
This paper seeks to analyze how work environment, job involvement, and job satisfaction influence turnover intention at PT. XYZ. The study involved 119 employees as respondents. Data were gathered through the distribution of questionnaires and analyzed using SmartPLS version 4.1.0.9. The findings suggest that the work environment positively and significantly influences turnover intention, whereas job involvement and job satisfaction exert negative and significant effects on turnover intention at PT. XYZ.